Renal cyst occurring in a case of Darier’s disease - Thomas, Vipul Paul; Sivaramakrishnan, Sangiah; Thomas, Jayakar (International Journal of Research in Dermatology, 2019)
Darier’s disease is a rare genodermatosis inherited in an autosomal dominant pattern. The disease is characterised by chronic persistent hyperkeratotic papular eruptions over the seborrheic regions.